Childhood mortality, intra-household bargaining power and fertility preferences among women in Ghana - Jacob Novignon; Nadege Gbetoton Djossou; Ulrika Enemark (Reproductive Health, 2019)
Abstract Background Continuing population growth could be detrimental for social and economic wellbeing. Understanding the factors that influence family planning decisions will be important for policy. This paper examines the effect of childhood mortality and women’s bargaining power on family planning decisions. Methods Data was from the 2014 Ghana Demographic and Health Survey (DHS). A sample of 3313 women in their reproductive age were included in this study. We created variables on women’s exposure to and experience of child mortality risks. Three different indicators of women’s bargaining power in the household were also used. Probit models were estimated in accordance with the nature of the dependent variable. Results Results from the probit models suggest that child mortality has a positive association with higher fertility preference. Also, child mortality risks and woman’s bargaining power play important roles in a woman’s fertility choices in Ghana. Women with higher bargaining power were likely to prefer fewer children in the face of child mortality risks, compared to women with lower bargaining power. Conclusion In addition to public sensitization campaigns on the dangers of high fertility and use of contraceptives, the findings of this study emphasize the need to focus on reducing child mortality and improving women bargaining power in developing countries.